Diversity of technical treatments in digital graphic design (Journal of the College of Basic Education, 2022)
Technical diversity is one of the most important design factors in showing the artistic image of the design achievement with its potential energy, through the technical, intellectual, expressive, functional and aesthetic orientation, presenting multiple display options that are consistent with what is in line with the design idea aimed at a subject. Technical diversity also confirms achieving a distinguished qualitative appearance of the accomplished. The design, which would enhance the effectiveness of the communication effect of the design advertising message, and that the diversity may be a difference in color, shape, texture, or direction, and it may be gradual in the thickness of the lines, and the contrast of colors